Programa didáctico centrado en el método científico y su influencia en el desarrollo de las habilidades lógicas de los estudiantes universitarios - Gutierrez Alva, Cesar Felipe (2019)
ABSTRACT The current world lives the called information age, because there is a wealth of data available in different written and electronic sources. However, this situation demands as a challenge domination of different mental operations to convert this information into useful knowledge in order to transform society. The problem posed was: To what extent a didactic program focused on the scientific method influences the development of the logical skills of the third year students of the Secondary Education, History and Geography career, National University of Trujillo, Peru -2018? The purpose of the study was to experience the influence of a didactic program in the development of logical skills. The design used to test the hypothesis was pre-experimental. The sample population was constituted by 26 students. The measuring instrument that was used was the questionnaire to evaluate the logical abilities of the students. After systematizing and analyzing the results, it was concluded that the proposed program for this study, influenced significantly in the development of the optimal level, located in the 4 evaluative scale, of the logical skills of the participants in this research work.